Green Human Resource Management Practices and Their Role in Enhancing Organizational Reputation: an Analytical Study of the Opinions of a Sample of Employees at a Food Industries Company Limited - Basim Naser Jaafar; Mouna Damak Turki (Research Parks Publishers, 2026)
The current research aims to investigate the role of green human resource management practices (green recruitment and selection, green participation, green training, green performance management, and green compensation and rewards) in enhancing organizational reputation across its dimensions (innovation, social responsibility, service quality, reliability toward the organization, and benevolence toward the organization) among a sample of employees at the Union Sugar Factory. The research sample consisted of (308) workers. A descriptive analytical approach was used to achieve the research objectives and develop its tools, using statistical programs (AMOS.V.29, SPSS.V.29). The research results revealed a significant correlation between green human resource management practices and organizational reputation. Accordingly, the research presented a set of recommendations and proposals based on the findings.